Challenges and Opportunities of Maritime Transport in the Post-Epidemic Era - Guangnian Xiao; Lang Xu (Journal of Marine Science and Engineering)
The global outbreak of COVID-19 has cast a protracted shadow over the international economic landscape, with maritime transport emerging as a cornerstone of resilience and adaptation [...]